Influence of pacing on reliability of middle-distance cycling performance - Aisbett, B.; LeRossignol, P.; McConell, G.; Jolley, D.; Abbiss, C. R.; Snow, R. (Journal of Science and Cycling, 2015)
The purpose of the present study was to examine the reliability of middle distance cycling time trials using fast-, even-, and slow-starts. Eighteen endurance-trained male cyclists [mean ± standard deviation; VO2peak 63.1 ± 6.1 mL/kg·min] performed nine cycling time trials where the total external work (96.5 ± 11.2 kJ) was identical to the better of two, 5-minute habituation time trials. Power output during the first quarter of the time-trials (24.1 ± 2.8 kJ) was fixed to induce fast-, even- or slow-starting strategies (60, 75 and 90 s, respectively). In consecutive sessions, participants performed three trials of each pacing condition although the order of these pacing conditions was counterbalanced. Average power output and performance time were unaffected by trial number in the fast- (P = 0.60), even- (P = 0.18) and slow-start (P = 0.53) trials. In all three pacing conditions, average power output was highly reliable and similar between trial 1 to 2 and trial 2 to 3 in fast- (standard error of measurement; SEM=8.3 and 8.2W), even (coefficient of variation; CV=2.8 and 2.4%) and slow-start (CV=2.4 and 1.5%) trials. In conclusion, the reproducibility of 5-min cycling time trials is unaffected by starting strategy and is acceptable following two self- paced habituation trials. Research examining the influence of pacing strategies may therefore be conducted without the need for familiarisation trials using each individual pacing condition.